Vocabulary acquisition for future nursing staff - Hempkin, Kirsten (Scripta manent (Ljubljana), 2012)
Research suggests that many ESL teachers either modify or supplement the set textbooks they use in class, or develop their own materials for classroom use. Indeed, in recent years, the internet in particular has opened up a rich and at times perhaps baffling array of resources for those ESL practitioners who wish to incorporate authentic materials into their teaching. While the benefits of authentic materials are well-documented, their use is, however, not entirely unproblematic, and as research into the field of material (authentic or otherwise) development grows, this raises a number of issues as to the form these materials should take and how they can best be employed. This article presents a set of vocabulary building activities for future nursing staff; these activities are in use at the Faculty of Health Sciences in Maribor. The article explains the rationale behind them in light of the theoretical framework of language acquisition that underpins them.
Keywords: avtentična gradiva; ESL teachers; graauthentic materials; ne zaključna dela; pouk angleščine; študenti zdravstvene nege; trainee nurses; usvajanje besedišča; vocabularyvocabulary acquisition; Vzgoja in izobraževanje; Zdravstvena nega; zdravstvo